The Impact of Educational Investment on Labor Productivity in Indonesia - Syamsu Rijal; Mustari (International Journal of Technology and Education Research, 2025)
This study aims to analyze in depth the impact of education investment on labor productivity in Indonesia over the past ten years. Education investment is viewed as a strategic element in human resource development, which ultimately contributes to national economic growth. This study uses secondary data obtained from the Central Statistics Agency (BPS) and the World Bank, which includes indicators of government spending on education and labor productivity levels. The analytical method used is linear regression to measure the relationship between these variables. The results show that increased investment in the education sector contributes significantly to increased labor productivity. Education not only plays a role in improving skills and technical competencies but also influences individual competitiveness in domestic and global labor markets. These findings strengthen the argument that effective and sustainable education policies are key to accelerating the transformation of a knowledge-based economy. Therefore, the government and stakeholders are expected to strengthen resource allocation and education programs that are more inclusive and relevant to current industry needs.